Climatic characteristics of extreme precipitation and its relationship with temperature during the warm season in Jiangxi province - Yanan Liu; Huabin Zhan; Qiong Wu; Lei Li; Yikun Feng (Geomatics, Natural Hazards & Risk)
The response of extreme precipitation (EP) to temperature exhibits pronounced scale-dependent characteristics under global warming. This study investigates the spatio-temporal characteristics of EP and its association with temperature across diurnal to interannual scales during the warm season (May-September) from 2001 to 2023 in Jiangxi, China. Results reveal that EP events are primarily concentrated in northeastern Jiangxi, with monthly maxima occurring in June and diurnal peaks observed between 17:00 and 20:00. On the interannual scale, the correlation between temperature and EP reveals a meridional dipole pattern—positive in northern Jiangxi and negative in the south. Quantitative results show that for per 1 °C increase in temperature, the frequency of EP events (EPF) increases by approximately 19.6%, while the intensity of EP (EPI) decreases by 0.66%, indicating an asymmetric thermodynamic response. On both daily and hourly timescales, EPA initially increases with temperature but declines beyond a threshold (∼25 °C daily, ∼27 °C hourly), with this suppression effect intensifying for longer-duration events. Furthermore, the relationships of specific and relative humidity (SH and RH) with temperature resemble that of EPI, increasing at lower temperatures but diverging at higher ranges, where SH follows CC scaling while RH declines more sharply.